Factors Impacting Resilience of Women Entrepreneurs in India in the Face of COVID-19 - Sukhjeet Kaur Matharu; Divya Juneja
Although enough research has been carried out on factors inspiring women to start and operate business, there is a need to assess the role of various factors impacting resilience of Indian women entrepreneurs. Women entrepreneurs all over the world are struggling, adapting diverse strategies and innovating in the face of COVID-19, to fight against the crisis and bouncing back to their normal stage. The present study aims at identifying the direct relationships among selected factors in influencing the resilience of women entrepreneurs. The sample for the study comprised 396 women entrepreneurs from different regions of India. This is a survey-based study; a self-administered questionnaire was used for the collection of data. Analysis of the data collected was done using analysis of moment structures based structural equation modelling. Findings of the analysis state a significant and positive influence of entrepreneurial characteristics, resourcefulness, networking, adaptability and continuity in forming the resilient attitude of women entrepreneurs when faced with a crisis situation. The study can be useful to women entrepreneurs, organizations, government and other institutions extending support to entrepreneurs.